Potential nutritive value of some tree leaves commonly used for small ruminant in the Aegean region of Turkey - Ünlü, Hayrullah Bora; Özkan, Çağrı Özgür; Kamalak, Adem (Progress in Nutrition, 2022)
The nutritional potential of the leaves of 10 different maquis tree species were evaluated in terms of chemical composition, in vitro gas and methane production, metabolizable energy (ME) and organic matter digestibility (OMD) in a maquis and mountainous region of western Turkey. Leaves from 10 tree species, Quercus aucheri, Olea europaea, Quercus robur, Morus alba L, Paliurus spina-christi, Pistacia terebinthus, Punica granatum, Pyrus elaeagnifolia, Vitis vinifera, and Tilia cordata, were sampled from maquis areas. Tree species had a significant effect on the chemical composition, in vitro gas, methane production, ME, and OMD (P<0.05). The results showed large variation in the contents of all examined nutritional components, in vitro gas and methane production, ME and OMD among the leaves of these tree species. Species had a significant effect on the chemical components, gas and methane production, ME, and OMD of tree leaves. The current study not only provides information about the chemical composition but also ME and OMD of tree leaves, making possible accurate formulation for ruminant animals grown in areas where tree leaves could be used as supplementary feeds for low-quality forages or substrate deficits. In particular, the nutritional value of the leaves of Morus alba L., Vitis vinifera, Pistacia terebinthus, and Paliurus spina-christi may offer considerable potential as high-quality forages and increase the economic proﬁtability of ruminants during critical periods in some semi-arid, arid, and maquis regions of Turkey. All tree leaves except for Olea europaea and Morus alba L. have a low or moderate potential and seems to be used as alternative feedstuffs to mitigate the enteric methane production. However, in vivo experiment is required to test the anti-methanogenic potential of tree leaves.